In colorectal cancer mast cells contribute to systemic regulatory T-cell dysfunction - Blatner, Nichole R.; Bonertz, Andreas; Beckhove, Philipp; Cheon, Eric C.; Krantz, Seth B.; Strouch, Matthew; Weitz, Jürgen; Koch, Moritz; Halverson, Amy L.; Bentrem, David J.; Khazaie, Khashayarsha (Proceedings of the National Academy of Sciences of the United States of America, 2010)
T-regulatory cells (Treg) and mast cells (MC) are abundant in colorectal cancer (CRC) tumors. Interaction between the two is known to promote immune suppression or loss of Treg functions and autoimmunity. Here, we demonstrate that in both human CRC and murine polyposis the outcome of this interaction is the generation of potently immune suppressive but proinflammatory Treg (ΔTreg). These Treg shut down IL10, gain potential to express IL17, and switch from suppressing to promoting MC expansion and degranulation. This change is also brought about by direct coculture of MC and Treg, or culture of Treg in medium containing IL6 and IL2. IL6 deficiency in the bone marrow of mice susceptible to polyposis eliminated IL17 production by the polyp infiltrating Treg, but did not significantly affect the growth of polyps or the generation of proinflammatory Treg. IL6-deficient MC could generate proinflammatory Treg. Thus, MC induce Treg to switch function and escalate inflammation in CRC without losing T-cell-suppressive properties. IL6 and IL17 are not needed in this process.
Gesehen am 13.02.2023